Governance and Leadership Wrappers of Constitutional Democracy: An Inaugural Lecture - Benon c., Basheka (Kabale University, 2022)
Aristotle’s said, “We must begin”, “by asking an old and fundamental question – whether it is better to be ruled by the Best man or by the Best Laws.” One may also pose at this juncture and ask: Whether we need a government? If the answer is in the affirmative, what form of Government do we need? Good things and bad things we see in society are caused by leadership and Public Administration!